Increased Precursor Cell Proliferation after Deep Brain Stimulation for Parkinson's Disease: A Human Study - Vedam-Mai, Vinata; Gardner, Bronwen; Okun, Michael S.; Siebzehnrubl, Florian A.; Kam, Monica; Aponso, Palingu; Steindler, Dennis A.; Yachnis, Anthony T.; Neal, Dan; Oliver, Brittany U.; Rath, Sean J.; Faull, Richard L. M.; et al. (PloS one, 2014)
Deep brain stimulation (DBS) has been used for more than a decade to treat Parkinson's disease (PD); however, its mechanism of action remains unknown. Given the close proximity of the electrode trajectory to areas of the brain known as the "germinal niches," we sought to explore the possibility that DBS influences neural stem cell proliferation locally, as well as more distantly. We studied the brains of a total of 12 idiopathic Parkinson's disease patients that were treated with DBS (the electrode placement occurred 0.5-6 years before death), and who subsequently died of unrelated illnesses. These were compared to the brains of 10 control individuals without CNS disease, and those of 5 PD patients with no DBS. Immunohistochemical analyses of the subventricular zone (SVZ) of the lateral ventricles, the third ventricle lining, and the tissue surrounding the DBS lead revealed significantly greater numbers of proliferating cells expressing markers of the cell cycle, plasticity, and neural precursor cells in PD-DBS tissue compared with both normal brain tissue and tissue from PD patients not treated with DBS. The level of cell proliferation in the SVZ in PD-DBS brains was 2-6 fold greater than that in normal and untreated PD brains. Our data suggest that DBS is capable of increasing cellular plasticity in the brain, and we hypothesize that it may have more widespread effects beyond the electrode location. It is unclear whether these effects of DBS have any symptomatic or other beneficial influences on PD.